Analisis Pengaruh Rasio Profitabilitas, Solvabilitas, Aktivitas, dan Pasar terhadap Harga Saham pada Perusahaan Manufaktur: Subsektor Plastik dan Kemasan yang Terdaftar di BEI - Esti Nur Hidayah; Bambang Sugeng Dwiyanto (Jurnal Manajemen Strategis: Jurnal Mantra, 2024)
This study aimed to examine the effect of Return on Asset (ROA), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), and Price to Book Value (PBV) on stock prices in manufacturing companies in the plastic subsector and packaging listed on Indonesia Stock Exchange year period 2015-2019. The population in this study were the manufacturing companies in the plastic subsector and packaging listed on the Indonesia Stock Exchange year period 2015-2019 that were 13 companies the sampling technique used in this study was purposive sampling method.  The samples taken were 9 companies that published financial reports during the study period. The data analysis tools used were the classic assumption test (linearity test, normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test), multiple regression analysis, F-test, t-test, and determination test. The results of this study indicated that the Return on Assets (ROA) had a positive effect but was insignificant on stock prices. The Debt to Equity Ratio (DER), and Price to Book Value (PBV) had a positive significant effect on stock prices. MeanwhileTotal Asset Turnover (TATO) had a negative significant effect on stock prices. Simultaneously, the effect of Return on Asset (ROA), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), and Price to Book Value (PBV) had a significant effect on stock prices in the plastic subsector and packaging of companies listed on Indonesia Stock Exchange year period 2015-2019.